The Value of (Stock) Liquidity in the M&A Market - Massa, Massimo; Xu, Moqi (Journal of Financial and Quantitative Analysis, 2013)
Abstract We study the value of stock liquidity in the market for corporate control and show that the target firm’s liquidity has an impact on the transaction itself and on the resulting merged entity. We use a sample of U.S. merger and acquisition (M&A) transactions (1987–2007) to show that acquiring a more liquid firm makes the stock of the acquirer more liquid. This has consequences for M&A activity and pricing. Public acquirers are more likely than private acquirers to acquire more liquid targets. Liquidity also translates into a greater likelihood of completing the deal and higher compensation for the target.